Patient safety and nurse managers’ competencies in decision making relating to rationing of care – the state of the art - Uchmanowicz, Izabella; Gurowiec, Piotr; Zeleníková, Renáta; Gurková, Elena; Jarošová, Darja; Zborowska, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2020)
To prevent potential health- or life-threatening events during patient care at every stage of hospitalisation, all possible causes that could lead to adverse events should be recognised by the highly qualified medical staff who are responsible for patient safety. The aim of this state-of-the-art paper is to summarise the issue of patient safety in the hospital and nurse managers’ competencies relating to rationing of care, and to discuss implementation of the evidence-based practice as the key foundation for the development and knowledge management of nursing care. Research evidence does not provide any innovative solutions to direct knowledge management in clinical settings. Therefore, we should implement innovative interventions to be developed and evaluated for the implementation of knowledge management. The fact is that a global lack of nurses leads to missed care, which is a common threat, and it manifests itself as a potentially dangerous medical error that deserves special attention. The influence of various factors on knowledge management and the roles of senior nurses have not been well recognised or researched. Moreover, it was shown that practical mediations in order to implement knowledge management need to be refined and assessed. This is especially true in contemporary, challenging work environments with a lack of time for further professional development due to an increas-ing workload.